The early retirement of newscasts women presenters in Colombia and Spain: The repudiation of female old age (2019)
The actual television, as a mass communication based on public image, maintains a series of sexual stereotypes that are also transmitted in the newscasts. In the following research article, a cross-cultural gender study of a descriptive nature about the physical characteristics and age of the presenters of the most relevant television news programs in Colombia and Spain is presented, based on the audience obtained by this type of programs. Results and conclusions: The most obvious conclusions of this work, is that in this specific labor context, with few exceptions, the age of women, unlike her male partners, is not associated with greater credibility, rigor or seriousness, being a clear discriminatory element that associates women with a simple complement of undoubted physical attractiveness. © 2019 Universidad Complutense de Madrid. All rights reserved.